Wie progressiv ist Deutschland? Das Steuer- und Transfersystem im Europäischen Vergleich - Andreas Peichl; Thilo Schaefer (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Deutschland wird häufig ein im europäischen Vergleich überdurchschnittliches Abgabenniveau bescheinigt. Da dies als eine der Hauptursachen für vergleichsweise schwaches Wachstum und hohe Arbeitslosigkeit gilt, werden in der wirtschaftspolitischen Debatte vermehrt Reformen des progressiven Steuer- und Transfersystems gefordert. Im Zentrum unserer Untersuchung steht die Frage, welche Unterschiede die Steuer- und Transfersysteme in den europäischen Ländern hinsichtlich ihrer Progressivität aufweisen und welche Wirkungen auf die Verteilung der Einkommen darauf zurückzuführen sind. Die Analyse zeigt, dass Deutschland im europäischen Vergleich insgesamt eher im mittleren Bereich anzusiedeln ist. Gleichwohl kann der deutschen Einkommensteuer eine relativ hohe Umverteilungswirkung bescheinigt werden, die jedoch auf eine vergleichsweise hohe Ungleichheit der Markteinkommen zurückführen ist. Gleichzeitig geht von den stark regressiv wirkenden Sozialversicherungsbeiträgen eine relativ hohe Belastung aus. – – [How progressive is Germany? Comparing the redistributive effects of tax benefit systems in Europe] - When comparing tax benefit systems across Europe, Germany is usually regarded as a country with a high level of taxes and contributions which is often seen as a main challenge for the economic performance of the welfare state in terms of growth and unemployment. Especially the progressive structure of the German income tax is subject to various criticisms in the ongoing policy debate in Germany. In this paper, we compare the progressivity and redistribution induced by the tax benefit systems in the EU-15 countries. In contrast to previous studies, we do not focus only on the income tax system but additionally consider social insurance contributions and cash benefits for a complete analysis of the whole tax benefit system. Our analysis is based on EUROMOD, a static tax benefit microsimulation model for the EU-15 countries, which allows analysing the tax benefit systems in a common framework. We compute several measures of progressivity and redistribution for the whole tax benefit system as well as for the single components. We compare the values of these measures across countries to rank the countries according to their progressivity and level of redistribution. Our analysis shows that there is considerable variety with respect to progressivity and redistribution across the countries. We show that the German system as a whole employs only a medium level of redistribution, which contradicts to some extent the existing German literature. However, this effect can be decomposed into a highly progressive income tax system, a highly unequal pre-tax income distribution and regressive social insurance contributions as well as regressive transfers. Therefore, when thinking of reforming the highly progressive income tax system, one has to take into account the regressive effects of the other elements of the tax benefit system.
Keywords: D31; H24; 330; Progression; Umverteilung; Steuer- und Transfersystem; Europäischer Vergleich; Steuerbelastung; Steuerprogression; Steuersystem; Sozialtransfer; Einkommensteuer; Sozialversicherungsbeitrag; Deutschland